2022
DOI: 10.18196/mb.v13i2.13947
|View full text |Cite
|
Sign up to set email alerts
|

Work-life Balance and Compensation on Performance with Job Satisfaction as an Intervening Variable for Millennial Generation Banking Employees

Abstract: Research aims: The research aims to determine the effect of work-life balance and compensation on performance with job satisfaction as a variable intervening of millennial generation banking employees in Semarang City.Design/Methodology/Approach: This research design is quantitative. This study’s primary data was obtained by distributing questionnaires to millennial-generation banking employees. The study was conducted for one month. Hypothesis testing in this study used the SEM-STATA method.Research findings:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 37 publications
6
4
0
Order By: Relevance
“…According to Robbins & Judge [12], employees who feel satisfied with their life at work tend to show higher levels of productivity. This is supported by the findings of Ingsih, et al [5] and Susanto, et al [6] that there is an influence between job satisfaction and performance. Therefore, the following proposition has been developed:…”
Section: H2: Training Has a Positive And Significant Effect On Perfor...supporting
confidence: 65%
See 4 more Smart Citations
“…According to Robbins & Judge [12], employees who feel satisfied with their life at work tend to show higher levels of productivity. This is supported by the findings of Ingsih, et al [5] and Susanto, et al [6] that there is an influence between job satisfaction and performance. Therefore, the following proposition has been developed:…”
Section: H2: Training Has a Positive And Significant Effect On Perfor...supporting
confidence: 65%
“…Victoria, et al [28] found that satisfaction at work can be obtained when an employee feels satisfaction and success in his family life. This is supported by the findings of Ingsih et al [5] and Mercado [29] that there is an influence between work-life balance and job satisfaction. Therefore, the following proposition has been developed:…”
Section: H3: Job Satisfaction Has a Positive Effect On Performancesupporting
confidence: 65%
See 3 more Smart Citations